Improving Learning Outcomes of Class VIII Students of SMPN 6 Kediri in Writing Poetry with the Development of Name Models - Sutirta, Eka (Efektor, 2019)
The process of learning Indonesian language in Class VIII-A of SMP 6 Kediri experienced several obstacles. The obstacle is that the teacher only gives assignments or tells students to write poetry without accompanied by unclear guidance on how to write the poem itself. Also because the learning source is only centered on the textbook. And what often happens is the students' low interest in poetry. After a daily test, it is known that only 53% of students have complete KKM grades. The data shows that student learning outcomes are quite low. One solution to overcome this problem, by developing the right name model is used. This model in its application has three steps that must be considered including the use of names; specify a name, and tell me the name. The application of poetry learning model names is done by collaborating with groups. This is done in order to grow honesty, participation, cooperation with students and groups etc. Writing poetry model names by using picture media in groups or collaboration with the following learning steps. Students work together in groups of 3-5 children. The teacher shares pictures (pictures of people, places/events etc.) with each group. Each student in the group receives a piece of paper to write poetry. Each group discussed to determine the name that corresponds to the picture obtained and the picture was an inspiration in writing poetry. The name that has been determined, each letter was originally made a line/poetry run. Each student in the group wrote an Acrostic poem/name based on the image. In this second cycle writing, Acrostic poetry is done individually. This is based on the observer's suggestion in the previous cycle. It turns out that student learning outcomes are more increasing than before. The indicator of the success of this study is that more than 75% of students pass the KKM. Based on the posttest results of students it can be seen that in the pre-cycle there were 53% (18) students completed KKM. Then, in the first cycle, there were 73.5% (25) students completed KKM. Then, in the second cycle, there were 82% (28) students completed KKM. The success of the study is in accordance with the indicators of success obtained in cycle II, which is more than 75% of students completed KKM. So it can be concluded that writing poetry with the development of the Name Model is able to improve the learning outcomes of Class VIII-A students in Kediri in Indonesian Language. even semester 2015/2016 school year.